Autophagy-dependent cancer cells circumvent loss of the upstream regulator RB1CC1/FIP200 and loss of LC3 conjugation by similar mechanisms. Issue 7 (2nd July 2020) - Towers, Christina G.; Wodetzki, Darya; Thorburn, Andrew
ABSTRACT: Macroautophagy/autophagy degrades proteins and organelles to generate macromolecular building blocks. As such, some cancer cells are particularly dependent on autophagy. In a previous paper, we found that even highly autophagy-dependent cancer cells can adapt to circumvent autophagy inhibition. However, it remains unclear if autophagy-dependent cancer cells could survive the complete elimination of autophagosome formation. We extended our previous findings to show that knockout (KO) of both the upstream autophagy regulator RB1CC1/FIP200 and the downstream regulator and mediator of LC3 conjugation, ATG7, strongly inhibits growth in highly autophagy-dependent cells within one week of editing. However, rare clones survived the loss of ATG7 or RB1CC1 and maintained growth even under autophagy-inducing conditions. Autophagy-dependent cells circumvent the complete loss of autophagy that is mediated by RB1CC1 KO, similar to the loss of ATG7, by upregulating NFE2L2/NRF2 signaling. These results indicate that cancer cell lines could adapt to the complete loss of autophagy by changing their biology to adopt alternative ways of dealing with autophagy-mediated cellular functions. Abbreviations: CGS: CRISPR growth score; CQ: chloroquine; CRISPR: clustered regularly interspaced short palindromic repeats; EBSS: Earl's balanced salt solution; EEF2: eukaryotic translation elongation factor 2; FOXO3/FOXO3a: forkhead box O3; GFP: green fluorescent protein; KEAP1: kelch Like ECH associated protein 1; KO: knockout; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MEFs: mouse embryonic fibroblasts; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; NLS: nuclear localization signal; PCNA: proliferating cell nuclear antigen; PE: phosphatidylethanolamine; POLR2A: RNA polymerase II subunit A; PTEN: phosphatase and tensin homolog; ROS: reactive oxygen species; SNARE: soluble NSF attachment protein receptor; SQSTM1: sequestosome 1; STX17: syntaxin 17; TBHP: tert-butyl hydroperoxide; ULK1: unc-51 like autophagy activating kinase 1; ULK2: unc-51 like autophagy activating kinase 2; WT: wild type